Numerical Study of Spherical Particle Breakage Based on Nonlinear Discrete Interface Bonded Model. (30th April 2022) - Li, Lin; Zhang, Sifeng; Yu, Shicai; Zhang, Xuanyu
Abstract : To study the contact mechanical characteristics and breakage mechanism of single particle, the particle contact experiment is simulated using the discrete element method. In this paper, to solve the problem that the envelope of the shear strength of the classical model is linear, a nonlinear discrete surface bonded model is introduced by applying nonlinear tangential strength criterion. The new model is compared with the classical model to verify its validity. Then, based on the new model, the particle contact experiment is numerically simulated, and the ball-plane contact breakage mechanism is analysed and discussed from the mesoscopic perspective. The results reveal that the nonlinear discrete interface bonded model can provide shear properties similar to those of actual materials. The numerical result reflects the shear failure of the edge of the conical region and the tensile failure of the whole specimen. Combined with the analysis of the results of stress distribution, velocity field, and force chain distribution, the formation mechanism of the cone core can be obtained.